2004
DOI: 10.1081/jcmr-200036108
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Reproducible Mitral Valvular Blood Flow Measurement with Three?Directional Velocity?Encoded Magnetic Resonance Imaging

Abstract: A new method for quantifying the transvalvular flow through the mitral valve (MV) based on three-directional velocity-encoded magnetic resonance imaging (MRI) is presented. For thirty time phases during one cardiac cycle, the three-dimensional (3D) velocity vector field of the blood flow is reconstructed from the MRI measurement. Retrospectively, for each time phase, the MV-plane is indicated manually in the velocity data and the flow through this plane is determined, representing the MV flow. Measurements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…However, conventional single-slice 1-directional VE-CMR showed some limitations (21), in particular because the acquisition plane cannot be adapted to the motion of the valve, and currently the most accurate approach is considered the 3D 3-directional VE-CMR with retrospective valve tracking. This technique is able to cover the complete velocity vector field of the blood flow and to correct for the through-plane myocardial motion in the apical-basal direction (22,23). Furthermore, it has been validated in vitro with flow phantoms and in vivo and showed excellent reproducibility (24).…”
Section: Quantification Of Mr Rt3de Versus 2d Echocardio-mentioning
confidence: 96%
See 1 more Smart Citation
“…However, conventional single-slice 1-directional VE-CMR showed some limitations (21), in particular because the acquisition plane cannot be adapted to the motion of the valve, and currently the most accurate approach is considered the 3D 3-directional VE-CMR with retrospective valve tracking. This technique is able to cover the complete velocity vector field of the blood flow and to correct for the through-plane myocardial motion in the apical-basal direction (22,23). Furthermore, it has been validated in vitro with flow phantoms and in vivo and showed excellent reproducibility (24).…”
Section: Quantification Of Mr Rt3de Versus 2d Echocardio-mentioning
confidence: 96%
“…Recently, velocity-encoded cardiac magnetic resonance (VE-CMR) has been proposed as a reference method for transvalvular flow quantification (19,20); in particular, the use of a 3-dimensional (3D) 3-directional acquisition has been shown to be able to optimize the conventional 2D 1-directional acquisition (21)(22)(23)(24), providing independent MR flow quantification. Therefore, the aim of the current study was to explore in patients with functional MR, the feasibility and accuracy of direct measurement of EROA and quantification of Rvol with RT3DE, in a head-to-head comparison with VE-CMR.…”
mentioning
confidence: 99%
“…The accuracy of flow measurement with MRI has been demonstrated in several in vitro studies and invasive in vivo measurements. 22,28 Therefore, although it may be debatable, MRI may be considered one of the reference methods to evaluate the accuracy of other imaging techniques in the assessment of regurgitant valvular lesions.…”
Section: Quantification Of Mitral Regurgitation Using 3d Tee Versus Mrimentioning
confidence: 99%
“…14 In fact, previous studies showed no conservation of mass and moderate correlations between stroke volume through the mitral valve (MV) and tricuspid valve (TV) and stroke volume measured in the ascending aorta. 15, 16 Kozerke et al 17 introduced the Slice Track-method where prior to VE MRI, the basal level of the left ventricle was labeled in the septum and the lateral wall and the excursion of the basal level determined the positioning and angulation of the acquisition. This technique makes use of navigator with prospective triggering for cardiac synchronization.…”
mentioning
confidence: 99%